Prospects for the application of intelligent automation in the pulp and paper industry - Gorobchenko Stanislav; Kovalev Dmitriy; Voinash Sergey; Zagidullin Ramil; Khafizov Ildar; Parfenopulo Georgy; Meshkov Sergey (E3S Web of Conferences)
The issues of using intelligent automation tools in the pulp and paper industry are considered. It is shown that the level of use of intelligent automation tools still remains insignificant. Promising directions for the implementation of intelligent automation tools in pulp and paper production have been identified. Areas where it is possible to obtain the most significant technical and economic effects from the introduction of intelligent automation tools have been identified. The main types of technical automation equipment that can be used to equip automated control systems in process control systems of the pulp and paper industry are demonstrated.